2015
DOI: 10.1088/1674-4926/36/12/122001
|View full text |Cite
|
Sign up to set email alerts
|

Variable range hopping conduction in n-CdSe samples at very low temperature

Abstract: Variable range hopping (VRH) conduction in the insulating three-dimensional n-CdSe samples has been studied over the entire temperature range from 0.03 to 1 K. In the absence of a magnetic field, the low temperature conductivity of the three samples (A, B and C) obeys the Mott VRH conduction with an appropriate temperature dependence in the prefactor ( D 0 exp OE .T 0 =T / p with p 0:25/. This behavior can be explained by a VRH model where the transport occurs by hopping between localized states in the vicinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The decrease in conductivity with a further increase in Zn was achieved because Zn introduces more additional scattering centers at the grain boundary which trap and scatter the conduction electrons and increases the height of the Schottky barriers, which therefore delay carriers' transport OE11 . The electrical transport in the insulating three-dimensional n-type CdSe samples was reported by Errai et al (2015) at low temperatures and found that the exponents are very close to 0.25 for all the samples. This shows that the electrical conductivity follows the hopping law and also indicates the existence of the regime Mott VRH without electron-electron interaction in the entire temperature range OE14 .…”
Section: Resultsmentioning
confidence: 81%
“…The decrease in conductivity with a further increase in Zn was achieved because Zn introduces more additional scattering centers at the grain boundary which trap and scatter the conduction electrons and increases the height of the Schottky barriers, which therefore delay carriers' transport OE11 . The electrical transport in the insulating three-dimensional n-type CdSe samples was reported by Errai et al (2015) at low temperatures and found that the exponents are very close to 0.25 for all the samples. This shows that the electrical conductivity follows the hopping law and also indicates the existence of the regime Mott VRH without electron-electron interaction in the entire temperature range OE14 .…”
Section: Resultsmentioning
confidence: 81%
“…It is difficult, therefore, to determine which of the hopping mechanisms is observed. Such a problem is commonly perceived for other materials and requires additional analysis [ 44 ]. In our case, we decided to use the M-VRH model due to the higher correlation coefficients 0.998 instead of 0.987 achieved for this model.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult, therefore, to determine which of the hopping mechanisms is observed. Such a problem is commonly perceived for other materials and requires additional analysis [44].…”
Section: Dc-conductivitymentioning
confidence: 99%
“…However, conclusions extracted from resistivity or conductivity are equally applicable. Semiconductors or any other insulating material have a natural temperature dependence of resistivity and can be written as [67]: where ρ DC (T) is DC resistivity, ρ o is a pre-exponential factor, T o is the characteristic temperature, and γ is the exponent whose value can be 1/2 and 1/4 and allows the profile of the density of states (DOS) to be determined. γ = 0.25 corresponds to Mott variable range hopping (VRH) in which hopping probability is optimized, and the defect DOS near the Fermi energy level is slowly varying [68].…”
Section: Electrical Transport Propertiesmentioning
confidence: 99%